تأثير الإجهاد الملحي في أصبغة التركيب الضوئي لصنفين من القمح الطري Triticum aestivum L. خلال مرحلة النمو المبكرة - عياش عبد الكريم; نصور رنا (Latakia University Journal -Biological Sciences Series, 2019)
أنجزت هذه الدراسة في مزارع رملية نقية بإضافة محلول مغذٍّ ضمن غرفة نمو مخبرية لمقارنة تأثير ملح كلور الصوديوم (100 ميلي مول) في أصبغة التركيب الضوئي عند صنفين من القمح الطري Triticum aestivum L. هما ACSAD 899 (حساس للملوحة) و ACSAD 1059 (متوسط التحمل للملوحة). تمت زراعة النباتات لمدة خمسة أسابيع وأجريت القياسات الفيزيولوجية في الأيام 21 ، 28، 35. لوحظ انخفاض نسبة الكلوروفيل أ (Chl. a) عند الصنف ACSAD 899 حتى بلغ أقل قيمة له في اليوم 35 من عمر النبات (48.5%)، أما عند الصنف ACSAD 1059 فقد ازداد تركيز Chl. a في بداية التجربة حتى بلغ أعلى قيمة له في اليوم 28 من التجربة بنسبة زيادة 3.6%، ثم انخفض في اليوم 35 من التجربة بنسبة 20%. ازداد تركيز الكلوروفيل ب (Chl. b) عند الصنفين ACSAD 899، ACSAD 1059 حتى اليوم 28 (5.4%، 29.3% على الترتيب). أما بالنسبة للأصبغة الكاروتينويدية (CAR) فقد لوحظ انخفاض تركيزها عند الصنف ACSAD 899 حتى بلغ أقل نسبة له في اليوم 35 من التجربة (41.9%)، بينما ازداد عند الصنف ACSAD 1059 خلال فترة التجربة حتى بلغ أعلى نسبة له (26.5%) في اليوم 35. This study was carried out in sand cultures irrigated with nutrient solution in a growth chamber to compare the effect of 100 mM of NaCl on photosynthetic pigments of two bread wheat cultivars: ACSAD 899 (salt sensitive) and ACSAD 1059 (moderately salt tolerant). The seedlings were cultivated for five weeks, and samples were analyzed in the days 21, 28, 35 of the experiment. Chlorophyll a (Chl.a) decreased under salinity conditions in ACSAD 899 and reached its lowest percentage in the day 35 (48.5%), while it increased in ACSAD 1059 and reached the highest value in the day 28 (3.6%) then it decreased in the day 35 (20%). Chlorophyll b (Chl.b) content increased in ACSAD 899 and ACSAD1059 until the day 28 (5.4%, 29.3% respectively). Concerning carotenoids content, it decreased in ACSAD 899 continuously under salt stress and reached the lowest value in the day 35 (46.9%), while it increased in ACSAD 1059 during the experiment and reached its highest percentage in the day 35 (26.5%).